Patients’ gut feelings seem useful in primary care professionals’ decision making - C. F. Stolper; M. W. J. van de Wiel; M. A. van Bokhoven; G. J. Dinant; P. Van Royen (BMC Primary Care, 2022)
Abstract Background Family physicians’ diagnostic gut feelings have proved to be valuable. But what about patients’ gut feelings? Research has shown that patients’ gut feelings may contribute to their physicians’ clinical reasoning. Dutch medical tribunals consider patients’ worry useful for doctors’ diagnostic process. However, how general practitioners and other primary care professionals recognize gut feelings of patients and deal with them in their decision making is yet unclear. We aim to explore how primary care professionals perceive patients’ gut feelings and use this information in their decision-making. Methods We interviewed 30 Dutch and Belgian primary care professionals, exploring how they recognize and value patients’ gut feelings. We coded all interviews using a descriptive content analysis in an iterative process. Data sufficiency was achieved. Results Primary care professionals acknowledged gut feelings in their patients, and most participants found them a useful source of information. Patients’ gut feelings might alert them to possible hidden problems and might provide quicker insight into patients’ perceptions. Primary care professionals listed a whole series of wordings relating to trusting or distrusting the situation or to any changes in normal patterns. A patient’s gut feeling was often a reason for the professionals to explore patients’ worries and to reconsider their own clinical reasoning. Conclusions Primary care professionals regularly considered patients’ gut feelings useful, as they might contribute to their clinical reasoning and to a deeper understanding of the patient’s problem. The next step could be to ask patients themselves about their gut feelings and explore their diagnostic value.